2020
DOI: 10.2147/jir.s282128
|View full text |Cite
|
Sign up to set email alerts
|

<p>Celecoxib Exerts a Therapeutic Effect Against Demyelination by Improving the Immune and Inflammatory Microenvironments</p>

Abstract: Background: The myelin sheath can be damaged by genetic and/or environmental factors, leading to demyelinating diseases, for which effective treatments are lacking. Recently, cyclooxygenase-2 (COX-2) overexpression was detected in demyelinating lesions both in patients and animal models, opening an avenue for promoting endogenous remyelination. The aim of this study was to investigate the therapeutic effect of celecoxib, a selective COX-2 inhibitor, against demyelination in a zebrafish model. Methods: The biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Estrogen, coupled with PGE 2 , could also induce hyperperistalsis in the EMI, which could further exacerbate injury to the SCs as well as compromise the barrier function of EMI, making it more receptive to invading cells. Additionally, COX-2, in itself, also plays an important role in SCs demyelination [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen, coupled with PGE 2 , could also induce hyperperistalsis in the EMI, which could further exacerbate injury to the SCs as well as compromise the barrier function of EMI, making it more receptive to invading cells. Additionally, COX-2, in itself, also plays an important role in SCs demyelination [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, if demyelination can be detected quickly, it will help prevent axonal damage when remyelination is promoted. There is increasing evidence that in ammation is necessary for myelin repair; recent studies have found that celecoxib has antidemyelinating effects and promotes myelin regeneration by improving the immune and in ammatory microenvironment [24].…”
Section: Discussionmentioning
confidence: 99%
“…M1 polarization is characterized by the secretion of proinflammatory cytokines and an increased expression of iNOS. The M1 microglial phenotype has been suggested as a cause or consequence of epilepsy [10,13,14] and is conducive to the onset of depression [8]. Polarization of microglia into the M2 phenotype, characterized by a higher expression of arginase-1 (Arg1), facilitates the release of various anti-inflammatory factors to enhance neuronal protection [15].…”
Section: Introductionmentioning
confidence: 99%